2021
DOI: 10.1016/j.eats.2020.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Combined Medial Patellofemoral Ligament and Medial Patellotibial Ligament Reconstruction for Recurrent Lateral Patellar Dislocation in Flexion

Abstract: Recurrent lateral patellar dislocation can be a challenging entity to manage. It results from an imbalance between the restraints to lateralization of the patella and the forces applied to the patella within the biomechanical environment of the knee. The medial patellofemoral ligament has been recognized as the most important static soft-tissue restraint. However, the medial patellotibial ligament and medial patellomeniscal ligament are important for patellar stability at higher degrees of knee flexion. Latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Our results are in line with other studies, such as the cadaver study by Nomura et al that showed that when a lateral displacement force (10 N) occurs, patella displacement is about 6 and 13 mm, respectively, with a normal medial patellofemoral ligament [80]. Other authors have demonstrated how lateral imbalance could reduce the force required to dislocate the patella by 10 mm at different angles, by approximately 20% [81].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in line with other studies, such as the cadaver study by Nomura et al that showed that when a lateral displacement force (10 N) occurs, patella displacement is about 6 and 13 mm, respectively, with a normal medial patellofemoral ligament [80]. Other authors have demonstrated how lateral imbalance could reduce the force required to dislocate the patella by 10 mm at different angles, by approximately 20% [81].…”
Section: Discussionsupporting
confidence: 92%
“…Lateral retinacular reconstruction may be performed using autograft or allograft tissue. This combined approach provides a more comprehensive stabilization of the patella and may reduce the risk of recurrent instability [28].…”
Section: Discussionmentioning
confidence: 99%
“…The higher dislocation rates seen in patients managed nonoperatively may be largely due to the MPFL being an essential structure, as it acts as a primary checkrein to lateral translation throughout the flexion arc [1]. Therefore, its absence even despite aggressive physiotherapy may contribute to the higher redislocation rates seen in the rehabilitation group.…”
Section: Discussionmentioning
confidence: 99%
“…In patellar dislocations, the Medial Patellofemoral Ligament (MPFL) is almost always ruptured [13]. The MPFL acts as a checkrein to lateral translation throughout the flexion arc [1], therefore, restoring MPFL structure and function is integral for treatment. This can be achieved through surgical, or non‐operative measures [32].…”
Section: Introductionmentioning
confidence: 99%